Bank managers' perception of the characteristics of successful entrepreneurs - Mahmood, Rosli; Mad Idris, Mohmad Amin (Malaysian Institute of Management, 2003)
The literature on the characteristics needed for entrepreneurial success has been widely discussed. Successful entrepreneurs have been found to possess a set of skills and attributes that include an ability to inspire others, autonomy and a high level of endurance. Entrepreneurs demonstrate a propensity to take risks and are ready for change.They also possess social skills such as persuasiveness, low need for support, low conformity and lack of emotionalism.The objective of this paper is to understand how successful entrepreneurial.characteristics are perceived from the perspectives of bankers.The finding may prove beneficial in the entrepreneurs' preparation of loan applications from banks.